2022
DOI: 10.3390/biom12091302
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Disordered Regions in Orchestrating the Properties of Multidomain Proteins: The SARS-CoV-2 Nucleocapsid Protein and Its Interaction with Enoxaparin

Abstract: Novel and efficient strategies need to be developed to interfere with the SARS-CoV-2 virus. One of the most promising pharmaceutical targets is the nucleocapsid protein (N), responsible for genomic RNA packaging. N is composed of two folded domains and three intrinsically disordered regions (IDRs). The globular RNA binding domain (NTD) and the tethered IDRs are rich in positively charged residues. The study of the interaction of N with polyanions can thus help to elucidate one of the key driving forces respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 87 publications
1
5
0
Order By: Relevance
“…Binding of NA (in the absence of NSP3a) appears to induce a different global conformational change in N-protein: In an NMR study, Pontoriero and colleagues ( 23 ) observed that binding of RNA to the NTD perturbs resonances in the LRS, and, measuring cross-talk between LRS and NTD in the absence of NA, they proposed intramolecular interactions to provide a regulatory mechanism for macromolecular interactions. Similar observations were made with a heparin ligand for the NTD ( 63 ). Unfortunately, the molecular details of this conformational change are still unclear.…”
Section: Discussionsupporting
confidence: 75%
“…Binding of NA (in the absence of NSP3a) appears to induce a different global conformational change in N-protein: In an NMR study, Pontoriero and colleagues ( 23 ) observed that binding of RNA to the NTD perturbs resonances in the LRS, and, measuring cross-talk between LRS and NTD in the absence of NA, they proposed intramolecular interactions to provide a regulatory mechanism for macromolecular interactions. Similar observations were made with a heparin ligand for the NTD ( 63 ). Unfortunately, the molecular details of this conformational change are still unclear.…”
Section: Discussionsupporting
confidence: 75%
“…Importantly, NP can rapidly spread by association with cell surface heparan sulfate proteoglycans (HSPGs) from infected to nearby uninfected cells, including cells resilient to infection (10). Indeed, in addition to RNA binding, NP was shown to bind to a soluble heparin analog, enoxaparin, as recently demonstrated by Nuclear Magnetic Resonance (NMR) (12). Cellular HSPGs often exhibit co-receptor roles due to their ability to bind multiple host ligands, receptors and signaling molecules in the extracellular space, as well as heterologous ligands, such as viruses through the sulfated polymeric glycosaminoglycans (GAGs) attached to serine residues of the protein core.…”
Section: Introductionmentioning
confidence: 90%
“…Importantly, NP can rapidly spread by association with cell surface heparan sulfate proteoglycans (HSPGs) from infected to nearby uninfected cells, including cells resilient to infection (10). Indeed, in addition to RNA binding, NP was shown to bind to a soluble heparin analog, enoxaparin, as recently demonstrated by Nuclear Magnetic Resonance (NMR) (12).…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsically disordered domains may be highly dynamic changing their conformations to favour antibody escape to protect the C-terminal CSP functions 42 43 . Docking recognition of intrinsically disordered repeats may be challenging, as shown for some viral nucleoproteins (i.e, 51 % intrinsically disordered nucleocapsid of SARS-CoV-2) [44][45][46] . On the other hand, some of the CSP disordered repeats may be conditional, getting some fold after additional protein interactions such as those spiral repeat conformations induced by mAb850 binding 18,19 .…”
Section: Is the Cross-docking Of α-Helices Csp Model-dependent?mentioning
confidence: 99%